ANALISIS PERBANDINGAN ALGORITMA LEVENSHTEIN DISTANCE DAN JARO WINKLER UNTUK APLIKASI DETEKSI PLAGIARISME DOKUMEN TEKS - Michael Julian Tannga; Syaiful Rahman; Hasniati (STMIK KHARISMA Makassar, 2017)
The goal of this study is to measure the performance comparison between Levenshtein Distance and Jaro Winkler algorithms to detect plagiarism in text documents. The test data that were being used in this study consisted of two test data, the test data to measure the similarity algorithms and test data to measure the processing time of the algorithms. The algorithm was tested by using plagiarism detection application to calculate the value of similarity and processing time by both algorithms. After testing, the results of the two tests are averaged and then analyzed the comparison. Results obtained for the comparative analysis of the average similarity of Jaro Winkler algorithm is 80.92%, while for the algorithm Levensthein Distance is 49.43%. Then, comparative analysis of the average processing time of Jaro Winkler algorithm is 0.054 seconds, while the average processing time of Levensthein Distance algorithm is 0.138 seconds. Based on the comparative analysis that has been done, Jaro Winkler algorithm is shown to have a higher similarity accuracy and the processing time is faster than the Levenshtein Distance algorithm in detecting plagiarsime document.